Changes in Genome-Wide Methylation and Gene Expression in Response to Future pCO2 Extremes in the Antarctic Pteropod Limacina helicina antarctica - Bogan, Samuel N.; Johnson, Kevin M.; Hofmann, Gretchen E. (Frontiers in Marine Science, 2020)
Epigenetic processes such as variation in DNA methylation may promote phenotypic plasticity and the rapid acclimatization of species to environmental change. The extent to which an organism may mount an epigenetic response to current and future climate extremes may influence its capacity to acclimatize or adapt to global change on ecological rather than evolutionary time scales. The thecosome pteropod Limacina helicina antarctica is an abundant macrozooplankton endemic to the Southern Ocean and is considered a bellwether of ocean acidification as it is highly sensitive to variation in carbonate chemistry. In this study, we quantified variation in DNA methylation and gene expression over time across different ocean acidification regimes. We exposed L. helicina antarctica to pCO2 levels mimicking present-day norms in the coastal Southern Ocean of 255 atm pCO2, present-day extremes of 530 atm pCO2, and projected extremes of 918 atm pCO2 for up to 7 days before measuring global DNA methylation and sequencing transcriptomes in animals from each treatment across time. L. helicina antarctica significantly reduced DNA methylation by 29–56% after 1 day of exposure to 918 atm pCO2 before DNA methylation returned to control levels after 6 days. In addition, L. helicina antarctica exposed to 918 atm pCO2 exhibited drastically more differential expression compared to cultures replicating present-day pCO2 extremes. Differentially expressed transcripts were predominantly downregulated. Furthermore, downregulated genes were enriched with signatures of gene body methylation. These findings support the potential role of DNA methylation in regulating transcriptomic responses by L. helicina antarctica to future ocean acidification and in situ variation in pCO2 experienced seasonally or during vertical migration. More broadly, L. helicina antarctica was capable of mounting a substantial epigenetic response to ocean acidification despite little evidence of metabolic recovery or transcriptional homeostasis in this species at future pCO2 levels.